Modeling wind energy development barriers: implications for promoting green energy sector - Cai, Jinyang; Ahmad, Munir; Irfan, Muhammad; Khan, Irfan; Razzaq, Asif (Energy sources. Part B, Economics, planning and policy, 2022)
Since a variety of barriers pose challenges to the Indian wind energy sector, the extent to which these barriers hamper this sector and the alternative solutions are largely unknown. We identify several barriers using existing literature, and then using the modified Delphi approach, refine 25 barriers and classify them into five significant dimensions. Later, the Analytical Hierarchical Process determined the ranking of barriers using pairwise comparison matrices. The Grey Technique for Order Preference by Similarity to Ideal Solution method ranked alternative solutions to these barriers. Results indicate that "financial barrier" is the most important barrier among all dimensions, while "limited government subsidy" is most influential among all sub-barriers. "Availability of adequate funds" is the best alternative to overcome these barriers. Finally, a sensitivity analysis is performed to validate the study findings. The study findings may assist practitioners and policymakers in boosting the current sluggish growth of the Indian wind sector.